Kinetics of pesticide degradation by human fresh frozen plasma (FFP) in vitro. (26th February 2016) - von der Wellen, Jens; Bierwisch, Anne; Worek, Franz; Thiermann, Horst; Wille, Timo
Highlights: We scrutinized degradation of pesticides by fresh frozen plasma in vitro . Degradation kinetics of pesticides were dependent on the different fresh frozen plasma batches. Fresh frozen plasma was not active against the phosphorothioamidate methamidophos and the phosphorothioates malaoxon and omethoate. Abstract: There is an ongoing debate about the benefit of fresh frozen plasma (FFP) infusion in organophosphorus (OP) pesticide-poisoned patients. This prompted us to investigate the kinetics of OP pesticide degradation by FFP with an enzymatic assay in vitro . Degradation was rapid with shortest half-lives of 19.5 s for chlorpyrifos-oxon, 6.3 min for paraoxon-ethyl and 17.9 min for dichlorvos. Heptenophos (78.0 min), mevinphos (101.8 min), profenofos (162.3 min) and malaoxon (179.7 min) showed half-lives of up to 3 h. Substantial longer degradation half-lives of 69.7–80.8 h were determined with chlorfenvinphos and bromfenvinphos. Methamidophos and omethoate showed no degradation by FFP indicated by half-lives similar to spontaneous hydrolysis. In conclusion, degradation by FFP depends on the particular OP pesticide and the used FFP batch.